Pengembangan Sistem Tracer Alumni dengan User Centered Design untuk Meningkatkan Usability Platform Digital - Febrianti, Ria; Akhsan, Rivaldi Rizalul; Isnandar (Institut Teknologi Garut, 2025)
Tracer studies are an essential instrument in the quality assurance system of vocational education, as they serve to track graduates’ whereabouts and achievements while providing a basis for curriculum improvement and collaboration with industry. The tracer study implementation at SMK Negeri 12 Malang is still manual and fragmented, resulting in alumni data that is difficult to organize and not optimally utilized. This condition highlights the need for a more efficient, structured, and user-friendly tracer study system. This study aims to develop a tracer study system prototype based on the User-Centered Design (UCD) approach using the Google Sites platform, and to evaluate its effectiveness and usability from the perspective of experts and end users. The development method follows the five stages of UCD: specifying the context of use, specifying user and organizational requirements, producing design solutions, and evaluating the design. Validation was carried out by media and content experts to assess the visual aspects and content relevance. The prototype was then tested by 15 alumni as primary users and evaluated using the quantitative System Usability Scale (SUS) method, complemented by qualitative think-aloud interviews. Expert validation results indicate that the system meets the principles of readability, visual structure, and content feasibility in accordance with vocational school tracer study standards. The trial results show that the system achieved an average SUS score of 77.67, classified as having “Good” usability, meaning it can be used easily and efficiently without requiring special training.